Synthesis and Antitumor Evaluation of Novel N-substituted Norcantharidin Imidazolium Derivatives - Sun, Rong-Rong; Guo, Jia-Hui; Yang, Cui; Yang, Li-Juan; Huang, Chao (Current Organic Synthesis, 2018)
Aims and Objectives: Cantharidin is a terpenoid with a high vesicant potency isolated from Mylabris caraganae and various other insects, which originates from the Chinese traditional medicine and has a long history of use as antiproliferative agent. Modified cantharidin derivatives are researched for retainable antitumor activities and lower toxicity. And imidazolium salt is an important building block in drug discovery with pharmacological activities. This study was undertaken to identify that N-substituted norcantharidin imidazolium derivatives possess potential bioactivity. Material and Method: Using readily available furan, maleic anhydride and imidazoles as starting materials, a series of novel N-substituted norcantharidin imidazolium derivatives have been designed and synthesized. The cytotoxic potential of all newly synthesized N-substituted norcantharidin imidazolium derivatives was assessed in vitro against a panel of human tumor cell lines, Human epidermal carcinoma, human lung carcinoma, liver hepatocellular carcinoma, pheochromocytoma of the rat adrenal medulla. Results: The imidazolium derivatives 6a-6f and 6m-6o, bearing a 5,6-dibromohexahydro-4,7-epoxyisobenzofuran- 1,3-dione or 5-bromo-7-oxabicyclo[2.2.1]hepta- 2,5-diene-2,3-dicarboxylate and electron-donating group, carbonyl and propenyl substituent at position-1 of the imidazole ring, were found to be the most potent compounds as antitumor agents. Notably, compounds 6m and 6n exhibited cytotoxic activity selectively against Hela and A549 cell lines with IC50 values 1.38-fold, 5.04-fold, lower than DDP, while compound 6f showed powerful inhibitory activities selectively against Hela and PC12 cell lines. Conclusion: Steric and electronic effects have an important role in determining the cytotoxic activity of imidazolium salts. The norcantharidin-imidazole 6f, 6m, 6n and 6o can be considered to be promising leads for further structural modifications guided by the valuable information derivable.
Keywords: imidazole